PENGARUH KOMITMEN, MOTIVASI, DAN LAYANAN PUBLIK TERHADAP KINERJA PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN TOJO UNA-UNA - Suaib, Namida (Katalogis, 2017)
Officials at The Secretariate of Regional Parliasment should show a good performance, in the sense of really mastering their job, because they have to support the assignments of the local legislators. Performance is the ability of employees in completing tasks assigned to him. An employee is capable of high performance if they have high motivation. Motivation is a process that directs employees to work better to complete work as expected. The study aims to determine and analyze simultaneous and partial influence of commitment, motivation, and public services on officials’ performance at The Secretariate of Regional Parliament of Tojo Una-Una District. Population consists of 35 respondents who selected through census method. Tool of analysis is multiple linear regressions. The study finds that commitment, motivation, and public services simultaneously and partially influence officials’ performance at The Secretariate of Regional Parliament of Tojo Una-Una District.